Pemadatan Tari Lagu Dhempel di STSI Surakarta - Nur Rokhim (Greget, 2010)
The Srimpi Lagu Dhempel dance is a traditional dance which grew and developed inside the palace walls. Originally this dance was not allowed to be performed outside the palace wallsÂ because of its exclusive nature and the strong sense of ownership within the palace. However, after the establishment of a number of art colleges in the 1970s, this dance began to be performed outside the palace, including at STSI Surakarta, which uses the dance as lecture material. STSI SurakartaÂ is an institution of higher education for the arts in Indonesia whose mission is to develop the life of Indonesian art and culture which is oriented to the future. As such, the tendency towards change must take place within a framework of creativity and possess a dynamic quality. In this case, one example of change is the endeavour to create an abridged version of the Srimpi Lagu Dhempel dance. The creation of shorter versions of existing dances at STSI Surakarta was pioneered by theÂ late Gendhon Humardani, and subsequently continued by many of his students. The abridgment of the Srimpi Lagu Dhempel dance was based on the concept of â€œcontainerâ€ and â€œcontentsâ€. The orientation of the abridgment is not time and the fact that the time becomes shorter is a result rather than the goal of the abridged version.Keywords : Abridgement, Srimpi Lagu Dhempel dance.